2015
DOI: 10.1007/s10961-015-9443-6
|View full text |Cite
|
Sign up to set email alerts
|

Support for public research spin-offs by the parent organizations and the speed of commercialization

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Spin-off survival depends on the quality and size of their parent companies (Fackler et al, 2016), technology transfer activities, normative frameworks, support infrastructures (i.e., business incubators and science parks), and TTO staff 's specialist technical skills (Berbegal-Mirabent et al, 2015;Ramaciotti and Rizzo, 2015;Fernández-Alles et al, 2015, Fini et al, 2011Bolzani et al, 2014;). Slavtchev and Göktepe-Hultén (2016) conclude that support in the early stage by the parent organization like helping in development of a business plan and in acquiring external capital can speed up commercialization. Commercialization plays signifi cant role in development and diff usion of technologies.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Spin-off survival depends on the quality and size of their parent companies (Fackler et al, 2016), technology transfer activities, normative frameworks, support infrastructures (i.e., business incubators and science parks), and TTO staff 's specialist technical skills (Berbegal-Mirabent et al, 2015;Ramaciotti and Rizzo, 2015;Fernández-Alles et al, 2015, Fini et al, 2011Bolzani et al, 2014;). Slavtchev and Göktepe-Hultén (2016) conclude that support in the early stage by the parent organization like helping in development of a business plan and in acquiring external capital can speed up commercialization. Commercialization plays signifi cant role in development and diff usion of technologies.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The MPS consists of 83 institutes and research facilities worldwide, of which 78 are situated in Germany and employ about 9,000 researchers in natural sciences, life sciences, and humanities. Within the public science sector in Germany, the MPS is complementing universities by performing research in fields that universities are not able to embed in their research agendas, especially in cases of new and innovative research that is uncertain, is of a basic nature, and requires long‐term commitment (i.e., structures and funding; Slavtchev and Göktepe‐Hultén ()). Research excellence of the MPS is documented by 33 Nobel Prizes since 1911.…”
Section: Research Setting: Max Planck Societymentioning
confidence: 99%
“…According to Jensen and Thursby (2002), most university technologies or research results are embryonic, requiring further development before they can be sold in the marketplace. Slavtchev and Göktepe-Hultén (2016) revealed that spin-offs supported by the parent organization in the early stages (i.e. nascent and seed) were able to generate their first revenues sooner.…”
Section: The Influence Of University-level Factorsmentioning
confidence: 99%